Структура и свойства твердого сплава ВК8, спеченного из порошков WC, обработанных ударными волнами - Ковтун, В.И.; Григорьев, О.Н.; Бега, Н.Д.; Волкогон, В.М.; Карпец, М.В.; Клименко, М.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
From powders WC treated by shock waves mixes of makeup BK8 are prepared, pressed and sintered at temperatures 1380 and 1450 °C samples. Structure of samples studied by methods of radiography and electron microscopy on a clearance. Have determined density of samples, microhardness Hμ, Vickers hardness Hv and Rockwell HRA, elastic modulus E, bending strength σben. and durability at shearing. The received results show, that shock-wave machining of powders WC results as to positive, and to negative changes in structure of corpuscles and sintered samples. And, dominant are negative
changes. To positive it is possible to relate formation in corpuscles WC nanosize subgrains, linear and dot defects, to negative – masstransmission atoms of carbon on a surface of corpuscles or for their breaking points. Thereof the carbide, isostructural WC is formed metastablis, with the lowered carbon content and the changed lattice parameters. Therefore physicomechanical and operational properties of samples BK8 appeared equal or is lower 20 % of the same properties of serial samples.